1862 Terr. of Wash. Stat. 284, ch. 2, § 30 - (:unkn) unknown (General Publisher, 1862)
Prohibited displaying any pistol, Bowie-knife, or other dangerous weapon to a crowd of two or more pesons in a rude, angry, or threatening manner.
--
Keywords: BRANDISHING